Tanggung Jawab Hukum Perusahaan Penyelenggara Ibadah Umrah - Fadilatun Nisa; Supriyadi Ahmad; M. Nuzul Wibawa (JOURNAL of LEGAL RESEARCH, 2019)
Abstract.This paper examines First Travel's responsibilities in terms of civil, criminal, administrative law for the alleged crime. The results showed that First Travel had committed a crime of fraud, embezzlement, and money laundering with the Umrah mode. This study uses a normative legal research method using the law approach and case approach. The results showed that the number of victims reached thousands of prospective Umrah pilgrims, with losses of up to billions of rupiah. The owner of First Travel is subject to imprisonment of twenty years and eighteen years and a fine of ten billion rupiah.Keywords: Responsibility, PT. First Travel, Jamaat, Failed to Leave